1995
DOI: 10.1055/s-2008-1066253
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Erythrocyte Antioxidant Enzyme Activities and Embryologie Level of Neural Tube Defects

Abstract: Increased exposure to oxidant-derived free radicals or inadequate systems for antioxidant defense could alter cellular response at critical points in development. We measured 5 antioxidant enzymes, glutathione peroxidase (GSH-Px), glutathione reductase, glutathione-S-transferase, catalase and superoxide dismutase in erythrocytes and their plasma cofactor trace elements (Se, Zn, Cu) in 37 children with myelomeningocele and in 37 age-matched controls. We placed the patients into 3 groups according to motor level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…Only a few articles describing abnormal FRSE activities in infants with MM have been published (6,7,8,10). Previous studies measured FRSE activities, especially GSH-related reported a similar observation.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Only a few articles describing abnormal FRSE activities in infants with MM have been published (6,7,8,10). Previous studies measured FRSE activities, especially GSH-related reported a similar observation.…”
Section: Discussionsupporting
confidence: 56%
“…There was significantly lower GPX activity in children with MM (7). The studies of Graf et al (7,10,21) indicated that deficiencies of GPX are directly linked to neural tube defects. More recently, Graf and colleagues have demonstrated that GPX can be depressed in valporoic acid-treated patients (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many drugs that cause neural tube, and other, defects, including thalidomide [56], phenytoin [56,57], environmental aryl hydrocarbons such as 2,3,7,8-tetrachlorodibenzo-p-dioxin [58], and ionizing radiation [59] induce oxidative stress. Myelomeningocele has been linked with reduced glutathione peroxidase activity apparently resulting from a genetic polymorphism [60]. Finally, maternal obesity, which could increase embryo oxidant exposure due to maternal glucose intolerance, has been found to increase the relative risk for NTD [61,62].…”
Section: Discussionmentioning
confidence: 99%